Listening At the Sea Ice Edge: Compositions based on soundscape recordings made in Antarctica - Philpott, C (Routledge, 2019)
This chapter examines compositions based on field recordings made in Antarctica by leading sound artists Douglas Quin and Philip Samartzis. Collectively, Quin and Samartzis have spent five summer seasons in Antarctica and have amassed substantial libraries of soundscape recordings featuring biological sounds (such as vocalisations of penguins and seals above the ice and underwater); geophysical ambient sounds that emanate from the icescape (such as those created by wind, blizzards and ice cracking and calving); and anthropogenic sounds from icebreakers and research stations. Both artists have used their field recordings to create a range of compositions that are experienced by large audiences in myriad contexts, from concert halls and festivals, to zoos and museums. Focusing on their compositions that incorporate sounds from underwater, as well as from above the ice, the chapter aims to shed light on what their works can tell us about a place that most people are unlikely to ever see or hear in person.